Waste disposal by aerobic oxidation - B A Koch (Kansas Agricultural Experiment Station Research Reports, 1970)
Waste disposal and odor control are two important problems in pork production. The odor formerly was called the "money smell" has suddenly become "Environmental Pollution." Concentrating many animals in small areas compounds the problem.; Swine Day, Manhattan, KS, October 1, 1970
Keywords: Swine day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 163; Swine; Waste disposal; Aerobic oxidation